2019
DOI: 10.3390/ma12233820
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Al2O3/Ti(C,N)/ZrO2/CaF2@Al(OH)3 Ceramic Tools and Cutting Performance in Turning

Abstract: Aiming at the contradiction between the lubricating performance and mechanical performance of self-lubricating ceramic tools. CaF2@Al(OH)3 particles were prepared by the heterogeneous nucleation method. An Al2O3/Ti(C,N) ceramic tool with CaF2@Al2(OH)3 particles and ZrO2 whiskers was prepared by hot press sintering (frittage). The cutting performances and wear mechanisms of this ceramic tool were investigated. Compared with the Al2O3/Ti(C,N) ceramic tool, the Al2O3/Ti(C,N)/ZrO2/CaF2@Al(OH)3 ceramic tool had low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The atoms are arranged in a highly ordered manner; hence, the strength of the whiskers is close to that of the theoretical value of the intact crystals. The common ceramic whiskers include Al 2 O 3 , 55 , 56 SiC, 57–60 boron carbide(B 4 C), 61 zirconium dioxide(ZrO 2 ), 62 , 63 aluminum nitride (AlN), 64 , 65 and silicon nitride (Si 3 N 4 ) 66 , 67 whiskers. These whiskers are widely used in medical devices due to their light weight, good toughness, high strength, and superior temperature resistance.…”
Section: Classification Of Whiskersmentioning
confidence: 99%
“…The atoms are arranged in a highly ordered manner; hence, the strength of the whiskers is close to that of the theoretical value of the intact crystals. The common ceramic whiskers include Al 2 O 3 , 55 , 56 SiC, 57–60 boron carbide(B 4 C), 61 zirconium dioxide(ZrO 2 ), 62 , 63 aluminum nitride (AlN), 64 , 65 and silicon nitride (Si 3 N 4 ) 66 , 67 whiskers. These whiskers are widely used in medical devices due to their light weight, good toughness, high strength, and superior temperature resistance.…”
Section: Classification Of Whiskersmentioning
confidence: 99%
“…They found that at a nano TiC particle size of 40 nm and a content of 4 vol%, the comprehensive mechanical properties of the ceramic materials were the best. Chen et al [ 24 ] found that the simultaneous addition of surface-modified calcium fluoride and zirconia whiskers to ceramic tools could improve their fracture toughness, realize the self-lubricating effect of props, and achieve a good balance between the self-lubricating function and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…According to the relevant literature, cutting force, 11 tool wear, 12 and surface roughness 13 are one of the research focuses of cutting, and they are directly related to the quality of products. 14 Cutting forces and surface roughness can be affected by chip thickness, tool angle, and cutting speed.…”
Section: Introductionmentioning
confidence: 99%